Short-term optimal load training vs a modified complex training in semi-professional basketball players - Freitas, T. T.; Calleja-Gonzalez, J.; Carlos-Vivas, J.; Marin-Cascales, E.; Alcaraz, P. E. (Journal of Sports Sciences, 2019)
This study investigated the effects on neuromuscular performance of a 6-week Optimal Load Training (OLT) and a novel modified Complex Training (MCT) (complex pairs: the same exercise using a moderate and an OL) in basketball players, in-season. Eighteen male athletes were randomly assigned to one of the protocols. Anthropometric measurements were taken to evaluate body composition. Lower- and upper-body maximum dynamic strength, countermovement jump (CMJ), standing long jump (SLJ), 10-m sprint and change of direction (COD) were also assessed. Moderate-to-large strength gains (presented as percentage change ± 90% confidence limits) were obtained for half-squat (OLT: 10.8 ± 5.3%; MCT: 17.2 ± 11.6%) and hip thrust (OLT: 23.5 ± 17.7%; MCT: 28.2 ± 19.0%). OLT athletes achieved likely small improvements in sprint (1.6 ± 1.6%) and COD (3.0 ± 3.2%). Players in the MCT attained likely moderate improvements in COD (3.0 ± 2.0%) and possibly small in SLJ (2.5 ± 4.6%). No protocol relevantly affected CMJ or body composition. An ANCOVA test revealed unclear between-group differences. In conclusion, both protocols increased basketball players` strength without the use of heavy loads (> 85% 1RM) and without impairing sprint, CMJ and SLJ performance. These findings suggest that basketball strength and conditioning professionals may use either method to counteract strength losses during the season.